How Islam rules in Iran: theology and theocracy in the Islamic Republic - Kamrava, Mehran (Cambridge University Press, 2024)
"Focusing on the jurisprudential and ideological foundations of the Islamic Republic state, this book explores the relationship between Islam and politics in postrevolutionary Iran. It can be read at several levels, from informed observers and specialists to readers interested in Islamic studies, state-religion relations, and Shia jurisprudence"--